(untitled) (Critical Romani Studies, 2022)
In order to consider how white privilege functions in late modernity, this article engages with issues of identity and political economy to theorise the impact of racist discourse on Roma, Gypsies, and Travellers in the United Kingdmom (UK). The article specifically problematizes the increasing aggregation of Roma, Gypsies, and Travellers as one community of difference in the UK. The article expresses the author’s concern that contemporary discourse and associated policy developments have racialized communities, and in doing so negated them through a failure to acknowledge the breadth of experience of Roma, Gypsies, and Travellers. The article makes a theoretical argument, evidenced by a comprehensive review of literature in the social sciences and key policy documents in the UK. It also incorporates an analysis of reports produced by UK government and civil society organisations over the past 15-year period. The article argues that the categorisation of Roma, Gypsies, and Travellers as one community of difference has occurred due to the embedded racism within contemporary European society that functions through and is augmented by neoliberal capitalist norms. In conclusion the paper argues that the norms of neoliberal capitalism, that are typified by individualism, competition, and the primacy of capital over human experience, allow the perpetuation of this racist discourse that is not challenged by narratives of inclusion but rather is augmented by them.